(untitled) - Freeman, Christopher (London, 1974)
This book introduce the rise of science-related technology. Innovation and the theory of the firm. Innovation and government.
Keywords: Đổi mới công nghệ,Technological innovations; Khía cạnh kinh tế,Economic aspects